2011
DOI: 10.1002/ffj.2088
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel malodour compounds in laundry

Abstract: We investigated malodorous compounds on clothes in daily use and identified, for the first time, middle-chain fatty acids responsible for the malodour often described as 'wet and dirty dust-cloth-like'. Application of a preparative fraction collector and gas chromatography-mass spectrometry of the acidic volatile fraction carefully isolated from used clothes revealed the newly identified odorants responsible for unpleasant odours. In particular, the olfactory threshold of 4-methyl-3-hexenoic acid (4M3H), which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 20 publications
2
39
0
Order By: Relevance
“…Until now microorganisms have been identified to be responsible for malodour in laundry [12,13] and few microorganisms have been isolated and identified to be characteristic for biofilms from washing machines [8]. It is a fact that the characteristics of washing procedures changed to low temperatures and detergents without bleaching agent are preferred [14].…”
Section: Introductionmentioning
confidence: 99%
“…Until now microorganisms have been identified to be responsible for malodour in laundry [12,13] and few microorganisms have been isolated and identified to be characteristic for biofilms from washing machines [8]. It is a fact that the characteristics of washing procedures changed to low temperatures and detergents without bleaching agent are preferred [14].…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, (E)-4-methyl-3-hexenoic acid has been determined to be an odor-active compound in some natural sources, such as yuzu (Miyazato et al, 2013) and kabosu (Tomiyama, Aoki, Oikawa, Sakurai, Kasahara, & Kawakami, 2012). Further, Takeuchi, Hasegawa, Ishida, and Kashiwagi (2012) have reported (E)-4-methyl-3-hexenoic acid as the key odorous component responsible for the malodor in laundry. In our study, among the seven sweat-like-odor active compounds, (E)-4-methyl-3-hexenoic acid, along with 3-methylbutanoic acid and 2-methylbutanoic acid, has a high FD factor value of 32.…”
Section: Resultsmentioning
confidence: 99%
“…An aliquot (100 l) of the bacterial suspension (10 6 CFU/ml) was inoculated onto small pieces (2 by 2 cm) of sterilized used-towel samples and incubated at 30 or 35°C for 1 day. The odor sensory test of the samples was performed by the method of Takeuchi et al (35) as follows. Three panelists who had been trained in the test for at least 3 years directly sniffed the samples and ranked the overall odor intensities of the samples.…”
Section: Methodsmentioning
confidence: 99%
“…In our survey in 2008, 86% of the respondents (580 women whose ages ranged from 20 to 60 and who lived in the Tokyo metropolitan district) reported detecting a "wet-and-dirty-dustcloth-like malodor" of laundry. Recently, Takeuchi et al (35) have identified the agent that is frequently detected in clothes with a strong malodor as 4-methyl-3-hexenoic acid (4M3H), which accounts for the sweaty and wet-and-dirty-dustcloth-like malodor. Although 4M3H is present in trace amounts (up to 5 g/50 g of cloth) in clothes, it contributes most highly to the overall strength of such a malodor (35).…”
mentioning
confidence: 99%
See 1 more Smart Citation